The Implementation of the Merdeka Curriculum Based on Islamic Values in the Formation of Students Religious Character at Anbata Elementary School, Medan - Husna, Nurul; Ristiani, Ristiani; Ramadhana, Taufiqur; Fantrika, Muhammad Randa; Siregar, Bahtiar (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the strategies for implementing the Merdeka Curriculum based on Islamic values at elementary school Anbata Medan and to examine its impact on students’ religious character formation. Methodology: This study employed a qualitative case study approach. Data were collected through participatory classroom and school-culture observations, in-depth interviews with the principal, teachers, and students, and document analysis of the operational curriculum and teaching modules. Data analysis followed interactive qualitative analysis techniques without the use of specific statistical software. Main Findings: The findings reveal that Islamic values are integrated through three main pathways: curriculum planning by embedding tawhid and adab into learning objectives and modules; co-curricular P5 projects, particularly “Building Body and Soul,” implemented through spiritual habituation and moral studies; and a school ecosystem that reinforces religious character through congregational prayer, Qur’anic memorization, and courteous school culture as a hidden curriculum. Novelty/Originality of this study: This study offers a novel integrative model demonstrating how the Merdeka Curriculum can be operationalized as a value-based character education framework grounded in Islamic principles at the elementary level. It advances existing knowledge by illustrating the synergy between formal curriculum planning, P5 projects, and school culture in shaping holistic religious character.